6 - Elèves-mères et rationalité de la sexualité et de la maternité à l’Ouest-Cameroun - Meli Meli Vivien; Gnintedem Tchoubou Richelle; Yong Lemoumoun Judeon Socrate (African Sociological Review, 2018)
Early motherhood among young girls is analyzed and understood from the prisms of social structures and different institutions that would force young people to reproduce (EDS, 1994, 2004, 2011, Rwenge, 1999c, 2000). Kobelembi 2005, Gnazegbo 2014). Although very relevant, these analysis obscure, to a certain extent, the capacity generating and producing the sexual and reproductive norms internalized by these girls (Bourdieu, 1980, 1987). The purpose of this contribution is to account for the complexity of the reproductive sexual practices of the student-mothers sandwiched between social constraints and individual rationalities, determinations and individual strategies. To this end, the methodology adopted consisted of a cross-fertilization of quantitative and qualitative information from the questionnaires and interviews respectively in the rural localities of 5 departments of the West-Cameroon region (Menoua, Bamboutos, Nde, Noun, and High Nkam). It shows that the mother-pupils play with the structures of sexual and reproductive socialization, which oscillate between social constraint and individual freedom, tradition and modernity, sanction and tolerance, legitimation and delegitimization. The structures of socialization, sometimes contradictory, offer room for maneuver through which these girls socialize and give a practical meaning to their sexual acts. These new “sexual ways of doing things” are pushing West Cameroon societies to readjust, while producing new family dynamics.